2001
DOI: 10.1007/bf02919542
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic lung volume reduction surgery for pulmonary emphysema patients with severe hypercapnia

Abstract: Patients with severe pulmonary emphysema accompanied by hypercapnia can gain relief and a better quality of life through volume reduction surgery and should not be excluded from surgical treatment simply based on this condition. Selection should involve a comprehensive view of the patient's condition that includes criteria such as the results of radiographic diagnosis and detailed pulmonary function tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Tsunezuka et al [2000] 3 >50 mmHg Decrease in PaCO 2 from 52 ± 1 mmHg to 48 ± 2 mmHg. Mitsui et al [2001] 6 ⩾60 mmHg Decrease in PaCO 2 from 70.4 ± 9.4 mmHg to 46.9 ± 3.4 mmHg. Improvement in pulmonary function.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Tsunezuka et al [2000] 3 >50 mmHg Decrease in PaCO 2 from 52 ± 1 mmHg to 48 ± 2 mmHg. Mitsui et al [2001] 6 ⩾60 mmHg Decrease in PaCO 2 from 70.4 ± 9.4 mmHg to 46.9 ± 3.4 mmHg. Improvement in pulmonary function.…”
Section: Discussionmentioning
confidence: 94%
“…Although hypercapnia was found to increase the mortality rate associated with lung volume reduction surgery, it did not clearly identify patients for whom surgery posed a substantially higher risk than medical treatment [National Emphysema Treatment Trial Research Group, 2001]. Other studies on lung volume reduction surgery [Argenziano et al 1996; Albert et al 1998; Wisser et al 1998; O’Brien et al 1999; Shade et al 1999; Tsunezuka et al 2000; Mitsui et al 2001] analyzing patients with hypercapnic respiratory failure showed improvements of hypercapnia, pulmonary function, exercise capacity, dyspnea and quality of life. The studies are summarized in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Between October 1996 and May 1999, 18 male patients with severe emphysema aged 65.2 ± 6.4 years (mean ± SD) underwent LVRS by video‐assisted thoracoscopic surgery using staple resection at the Tohoku University Hospital (LVRS group) 11,12 . Each patient underwent bilateral simultaneous procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Several investigators have suggested impaired outcome and higher mortality in patients with hypercapnia, 81,93,201,202 whereas others have not confirmed this finding. 102,[203][204][205][206] The most definitive data come from the NETT where baseline paCO 2 was not associated with impaired outcome despite over 30% of randomized patients exhibiting baseline hypercapnia. 20 Figure 7 Kaplan-Meier estimates of the probability of death as a function of the number of months after randomization in the National Emphysema Treatment Trial (NETT) in (A) high-risk patients, (B) patients with upper lobe predominant emphysema and low, postrehabilitation exercise capacity, and (C) patients with non-upper lobe predominant emphysema and high, postrehabilitation exercise capacity.…”
Section: Physiological Featuresmentioning
confidence: 99%